Ocular Pathologies and the Evil Eye in the Early Roman Principate - Alvar-Nuño, Antón (Brill, 2012)
Ocular pathologies are a natural phenomenon that can be detected empirically. All over the world, such phenomena are often interpreted as an index of inherent personal capacity for causing harm. The Graeco-Roman world was no exception. During the early Roman Principate, the literary representation of such malformations was clearly influenced by two genres that had been developed in the Greek world during the Hellenistic period. The first was the paradoxographic or mirabilia tradition, a literary genre that in the aftermath of Alexander’s conquests inventorized supposed natural and anthropological wonders, reports that were subsequently brought up to date and adapted by Roman authors such as Cicero and Varro. The second was physiognomics, the systematization, mainly by the Peripatetics but also by some Hippocratic authors, of the popular idea that ethical character can be read from somatic signs. This paper understands Pliny the Elder’s accounts of peoples and families able to cast the evil eye, objectified in the possession of a double pupil, as a significant aspect of his socio-moral account of the effects of world-empire upon Rome. In transposing the theme to his figure of the procuress Dipsas almost a century earlier, Ovid created a synecdoche for moral disorder at Rome itself shortly before the two Augustan laws of 18 BCE regulating sexual conduct. In short, if we are to progress in our understanding of Roman socio-moral instrumentalization of ocular malformation in relation to the evil eye, we must pay careful attention to the contexts and strategies of our texts.
https://openpolicyfinder.jisc.ac.uk/id/publication/530
Keywords: Mal de ojo; Brujería - Roma; Fisiognomía; Evil eye; Jettatore; Ocular pathologies; Paradoxography; Physiognomic; Witchcraft